Proceso de ASC - ESTUDIO E IMPLEMENTACION DE UN SISTEMA DE IMPRESION HOLOGRAFICO DIRECTO PARA LA EXPLORACION Y APROPIACION DE LA HOLOGRAFIA SINTETICA. (2022)
Synthetic holography is an advancement in traditional holographic techniques aimed at overcoming a fundamental limitation: the physical constraints of objects. By integrating more complex components and sophisticated systems, synthetic holography expands the range of possible scenes that can be represented on these 3D displays. Therefore, this research project aims to adopt synthetic holography as a three-dimensional display technology, exploring its fundamental concepts and investigating new possibilities it can offer to the semillero.